توزيع الأموال المشتركة بين الزوجين بعد فصل الزواجفي الفقو الإسلامي)دراسة نقدية على كتاب مجموعة الأحكام الإسلامية، رقم : 9، في إندونيسيا(قدمت ىذه الرسالة لتكملة شروط الحصول على شهادة ماجستيرالشريعة الإسلامية في قسم الفقو وأصولوThe dividend of Community property among of man and wife after separation (property acquired jointly) in Islamic fiqih review - , Jumadi, Dr. M. Muinudinillah Basri, M.A, Dr. Muslih Abdul Karim, M.A (2014)
Indonesian government determined in Islamic law of compilation, no: 97, in the dividend property acquired jointly, that man and wife obtain half of the property, along undecided when marriage settlement and I mean this dividend is unjust and make the reason writing this thesis. The method which I used in this thesis is literation study with emphasize to analysis and critic study with compare KHI's decision what is at Islamic fiqih. There is important point and conclusion/result of this thesis is Indonesian government's decision in Islamic law of compilation, no: 97, less the property which obtained by man and wife, whereas in Islamic fiqih give the solution related dividend property acquired jointly with discussion system and sincere both of them.